Kansas environmental regulations - Joseph P. Harner; L. Hess; James P. Murphy (Kansas Agricultural Experiment Station Research Reports, 1995)
The Kansas Department of Health and Environment (KDHE) enforces two different regulation s in the state of Kansas. One set of regulation s is from the Federal Environmental Protection Agency (EPA) and applies to larger operations. The other is a set of Kansas regulation s created by our state legislature for smaller operations. EPA regulations pertain to confined feeding operation s in excess of 1,000 animal units and require an EPA National Pollution Discharge Elimination System (NPDES) permit. Because an animal unit for the NPDES permit is defined as one beef animal, a feedlot with a capacity of 1,000 or more will need to apply to KDHE for a NPDES permit. The main criterion of the permit is to contain the runoff volume from a 24-hour, 25-year frequency rainfall event.
Keywords: Cattlemen& #x27; s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Operations; Environmental regulations